8v-4=-12+7v

Simple and best practice solution for 8v-4=-12+7v equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8v-4=-12+7v equation:


Simplifying
8v + -4 = -12 + 7v

Reorder the terms:
-4 + 8v = -12 + 7v

Solving
-4 + 8v = -12 + 7v

Solving for variable 'v'.

Move all terms containing v to the left, all other terms to the right.

Add '-7v' to each side of the equation.
-4 + 8v + -7v = -12 + 7v + -7v

Combine like terms: 8v + -7v = 1v
-4 + 1v = -12 + 7v + -7v

Combine like terms: 7v + -7v = 0
-4 + 1v = -12 + 0
-4 + 1v = -12

Add '4' to each side of the equation.
-4 + 4 + 1v = -12 + 4

Combine like terms: -4 + 4 = 0
0 + 1v = -12 + 4
1v = -12 + 4

Combine like terms: -12 + 4 = -8
1v = -8

Divide each side by '1'.
v = -8

Simplifying
v = -8

See similar equations:

| 0.32x+0.23=0.40x+6 | | -6r=-18 | | Ax+5y=20 | | 3x=1y+2 | | -9+2.5y-0.7+1+6.4y= | | 4(p+7)=36+5p | | 7z+8=6z | | (2-7x)=(2x+1) | | 4(x+7)=36+5p | | 18-12x=-22-7x | | 3p(r+1)=7r-8t | | 7p-3=34 | | 12-36x-6x-24=-12 | | 5(9x-5)+12x= | | g(2)=7x-4 | | 2x+3y=4z-3xy | | 5a+35-12a-3=12-12a | | 2+3(-8n+6)=116 | | 125+15m=800 | | 10x+90=8x | | 3+(6x+4)=9 | | 2x+x-250=2858 | | 3(3Y-5)Y=-15 | | 8y-5x=27 | | 3a+15=3(a+5) | | 7=8(x+4)-2x | | 13-8b=-4b+5 | | 460g+g=11g | | 4-3(2-y)=y-2(3y-7) | | 18x+(-8+23)=5x(3+4) | | x-3x=60 | | -75+W=0 |

Equations solver categories